TINGKAT PENGETAHUAN MAHASISWA TENTANG PENGGUNAAN OBAT YANG BAIK DAN BENAR PADA JURUSAN FARMASI POLTEKKES KEMENKES ACEH TAHUN 2023 - Sari, Amelia; Burdah; Irwani, Maria; Aroni, Defri (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Medicine is a very important compound used for the prevention and cure of disease. Good and correct drug use is the use of drugs that are tailored to the clinical needs of patients, both adequate amount and time. Limited knowledge about the correct use of drugs is very dangerous, because if it is wrong to use drugs, it will have fatal consequences for ourselves or drug consumers. This study aims to determine the level of knowledge of students of the Department of Pharmacy Poltekkes Kemenkes Aceh about the use of good and correct drugs. this research is descriptive quantitative with a cross sectional approach. The sample in this study were third year students, totaling 84 people. The results of data analysis obtained that the knowledge of students of the Department of Pharmacy Poltekkes Kemenkes Aceh about the use of good and correct drugs is in the good category as many as 61 respondents (72.6%). So it can be concluded that students of the Department of Pharmacy Poltekkes Kemenkes Aceh have good knowledge about the use of good and correct drugs.